Effect of multispecies swards on ruminal fermentation, methane emission and potential for climate care cattle farming − an in vitro study - M.U. Hassan; P. Sidoruk; D. Lechniak; M. Szumacher-Strabel; J. Bocianowski; S. Ślusarczyk; P.R. Hargreaves; D. Ruska; A. Dorbe; Dz. Kreismane; K. Klumpp; J. Bloor; et al. (Animal)
Greenhouse gas (GHG) emissions from livestock ruminants, particularly methane (CH4), nitrous oxide, and indirectly ammonia (NH3) significantly contribute to climate change and global warming. Conventional monoculture swards for cattle feeding, such as perennial ryegrass or Italian ryegrass, usually require substantial fertiliser inputs. Such management elevates soil mineral nitrogen levels, resulting in GHG emissions and potential water contamination. Mitigating the environmental footprint of these farming practices requires sustainable alternative feeding strategies for cattle production. Multispecies grassland swards (grass + legumes or legumes + herbs) represent a promising alternative to monoculture grassland swards for cattle nutrition due to their reduced nitrogen requirements, excellent herbage yield, and polyphenolic compounds (tannins, formononetin, luteolin, quercetin, and acteoside) which may have positive effects on animals. This study investigated the effects of selected multispecies grassland swards (plant blends) on in vitro ruminal fermentation and DM digestibility. Three experimental blends of plants cultivated without fertilisers were utilised: (1) perennial ryegrass (PRG) + red clover (RC), (2) chicory (C) + red clover (RC), and (3) Tonic plantain (PLA) + red clover (RC). The control blend included perennial ryegrass (PRG), and red clover (RC) cultivated with fertiliser. The in vitro trial showed a reduction in CH4 production and ruminal NH3 concentration (by 14.7 and 28.8%, respectively; P < 0.01) in the PLA+RC blend compared to the control. This plant blend also increased propionate concentration (P < 0.05) and reduced acetate and butyrate concentrations and the acetate-propionate ratio (P < 0.01). Additionally, the total protozoal and methanogen counts were mostly reduced by the PLA+RC blend (P < 0.01) among all blends investigated. In conclusion, the Tonic plantain and red clover blend (PLA+RC) cultivated without fertilisers have the potential to be utilised as a sustainable alternative feed source for climate-friendly cattle production, aligning with the aims of the European Climate Care Cattle Farming project.